Hindfoot Nail or Protibial Screw Fixation for Ankle Fracture: A Multi-Centre Study. Issue 4 (November 2022) - Bethel, Jordan L.; Najefi, Ali-Asgar; Davies, Monica; Gosney, Eleanor; Patel, Keval; To, Christopher; Guryel, Enis; McEwan, Josephine; Buchan, Stephanie; Northway, Joseph; Quereshi, Amir; Ahluwalia, Raju
Category: Ankle; Trauma Introduction/Purpose: Multi-centre assessment of utilisation and outcomes of hindfoot intramedullary fixation (HFN) or fibula pro-tibial screw fixation (PTS) in complex ankle fractures. Methods: From January 2020 - June 2021, demographic data, co-morbidities, was collected on all patients undergoing HFN or PTS for an AO44 ankle fracture at three Major Trauma Centre's (MTC's) in the UK. Outcomes of interest included post-operative complications, Charlson-Co-morbidity-Index-Score (CCIS), weight-bearing status, peri-operative information, soft tissue management and post-operative complications were recorded, Radiographs were assessed for metalwork breakage and anatomical reduction (Pettrone Criteria). Results: 77 patients were identified; 59 underwent HFN and 18 had PTS fixation. The mean age differed between techniques (80+-11.4 [HFN] vs. 66+-19.8 [PTS]) (p<0.001) and 10-year survival favoured patients undergoing PTS (30+-31.6% in the [HFN] and 55+-37.6%[PTS] (p<0.004). 17 (29%) HFN patients had diabetes compared with 7 (39%) PTS patients. 36 (61%) HFN's were open fractures, 7 (39%) PTS's were open fractures, differences in outcomes between primary closure/shortening/joint preparation and combined ortho-plastic management were noted in the HFN group.Time to full weight bearing was reduced in HFN vs. PTS (2.1+-3.1 vs. 8.0+-5.0) (p<0.001), only a minority of patients were allowed to WB immediately. 12 (27%) of patients with open fractures had post-operative complications compared with 5 (15%) of closed fractures. The mean Pettrone score for HFN was 1.3+-1.6 compared with 3.7+-0.6 for PTS, subgroup analysis showed Pettrone scores for open fractures treated with a HFN worsened(0.9 vs 2.3) (p=0.007). Conclusion: Comparing functional and outcome rates between the 2 techniques, PTS provides stable fixation, and a lower overall complication rates, with better radiological outcomes and expected survival. However, HFN is performed in frailer patients, with co-morbidities where early weight-bearing may be beneficial, accepting limited functionality and higher complication rate. Even though both techniques are designed for early mobility in the appropriate person this is not always realised, thus further studies are required to characterise which patients benefit most from each surgical technique.